Kinerja Perusahaan dan Corporate Social Responsibility: Peran Moderasi dari Perusahaan Keluarga - Anita Anita; Maissy Maissy (Global Financial Accounting Journal, 2022)
Purpose - Corporate Social Responsibility (CSR) can be defined as a commitment and form of action taken by a company regarding social responsibility and the surrounding environment with the aim of improving the welfare of people's lives and strengthening relationships between stakeholders. The purpose of this study is to examine the relationship between firm performance and CSR moderated by family firm variables and firm size, leverage, and equity ownership concentration as control variables. Research Method - The sample used in this research is quantitative data with a purposive sampling technique. Based on the criteria, the number of samples collected is 240 samples from 48 companies in the period 2016-2020. The sample data is tested using panel data regression. Findings - The result of this study indicates that there is a significant negative relationship between the firm performance variable on CSR. The moderating variable, family firm, strengthens the relationship between firm performance and CSR. Implication - The findings of this study imply that the higher the firm performance and profits obtained from stakeholders, the company must also be more serious in paying attention to CSR issues, implement and disclose them following the demands of stakeholders instead of exploiting them more. Stakeholders must pay more attention, especially to family companies. Policymakers to evaluate existing regulations of CSR. They should encourage the implementation and disclosure of CSR in Indonesia, which will be beneficial for stakeholders and the company itself.